Multi-criteria investment prioritization using AHP: evidence from regional development - Christ Windreis (Indonesian Institute For Counseling, Education and Therapy, 2026)
Regional investment plays a critical role in promoting sustainable economic development by improving regional competitiveness, generating employment, and supporting long-term economic growth. This study aims to determine strategic investment priorities in Pekanbaru City, Indonesia, using the Analytic Hierarchy Process (AHP) as a multi-criteria decision-making approach. A descriptive quantitative research design was employed, involving twelve experts from government institutions, investment agencies, financial institutions, business associations, and private investors. Primary data were collected through structured interviews and pairwise comparison questionnaires, while secondary data were obtained from official government reports. The analysis evaluated five investment decision criteria, namely policy, economic, technical, environmental, and human resource dimensions. The results reveal that the policy criterion is the most influential factor in investment decision-making, followed by economic, technical, environmental, and human resource criteria. The final AHP synthesis identifies the trade sector as the highest regional investment priority, followed by the services and industry sectors. Sensitivity analysis confirms that the investment ranking remains stable under moderate changes in criterion weights, indicating the robustness of the decision model. The findings provide practical guidance for strengthening regional investment competitiveness through institutional reform, infrastructure development, environmental governance, and human resource capacity building.